PENDEKATAN THEORY OF CONSTRAINTS UNTUK PENINGKATAN LABA - Hanifatul Hasanah; Annisa Fatimah; Kurnia Ekasari (Universitas Gajayana Malang, 2020)
The purpose of this research is to analyze the company’s constraints by using the five steps of the Theory of Constraints. This is a descriptive quantitative research. Step one is to identify constraints, determine the most profitable product composition, maximize production flow with existing constraints using Takt Time Method, add capacity to constraints and redesign production processes. The results of this study indicates that in the production process, there are resources that experienced constraints. The constraints occured in the assembly process precisely in the second work station, that is the installation process of stepped gland and seal. The available time in August and September was 608,400 seconds while the time required in August is 637,900 seconds and 638,800 seconds in September which means, there was a constraint in the available time. In addition, profits generated by PT. Alinco is larger after the implementation of TOC than before. If the company use TOC, the profit that company achieve will increase amounted to IDR 1,056,200 in August and IDR 1,091,600 in September. Based on the analysis on the production cost, we can conclude that TOC can increase the profit.